15.7k views
5 votes
Q. # .,12 please I need help

Q. # .,12 please I need help-example-1

2 Answers

4 votes

Answer

= -16 + 72c


Step-by-step explanation

(2 - 9c)(-8) = (2 × -8) - (9c × -8)

= -16 - -72c

= -16 + 72c

User Toby Liu
by
5.1k points
4 votes

Consider the expression
(2-9c)\cdot(-8).

Use the distributive property


a\cdot (b-c)=a\cdot b-a\cdot c

to simplify your expression:


(2-9c)\cdot(-8)=2\cdot (-8)-9c\cdot (-8)=-16+72c.

Answer: correct choice is A.

User Slavo Vojacek
by
5.1k points